Ventral rectopexy with biological mesh: short-term functional results - Brunner, Michaela; Roth, H.; Guenther, K.; Grützmann, Robert; Matzel, K. E. (International Journal of Colorectal Disease, 2018)
PURPOSE: Ventral mesh rectopexy (VMR) is an established, minimally invasive, nerve-sparing procedure for the treatment of various symptomatic morphological changes in the posterior pelvic compartment. We present the short-term functional outcome and patient satisfaction after laparoscopic and robotic VMR with biological mesh. METHODS: We analyzed data from 123 patients who underwent laparoscopic ventral mesh rectopexy (LVMR) or robotic ventral mesh rectopexy (RVMR) from August 2012 to January 2017. Included in these data were patient demographics, intra- and postoperative findings, Cleveland Clinic Constipation Score (CCCS), Obstructed Defecation Score Longo (ODS), Cleveland Clinic Incontinence Score (CCIS), and patient satisfaction as measured by visual analog scale (0-10). RESULTS: Improvements in CCCS, CCIS, and ODS were statistically significant at 6 and 12 months (p < 0.001). Patient satisfaction was excellent at 6 and 12 months (8.2/10 and 8.3/10, respectively). The overall complication rate was 14%, with a major complication rate of 2%. No mesh-related complications were observed. The need for surgical re-intervention because of relapse, symptom persistence or recurrence, or new symptoms was 3%. Outcome appears to be similar between LVMR and RVMR. CONCLUSIONS: Both LVMR and RVMR with biological mesh are safe and effective in reducing symptoms, as measured by CCCS, CCIS, and ODS, and patient satisfaction is high.
EVALuna2:212626